2021
DOI: 10.1111/jdv.17351
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and safety of systemic therapies used in moderate‐to‐severe atopic dermatitis: a systematic literature review and network meta‐analysis

Abstract: Given the lack of head-to-head studies of systemic therapies in moderate-to-severe atopic dermatitis (AD), network meta-analyses (NMAs) can provide comparative efficacy and safety data to inform clinical decision-making. In this NMA, eligible randomized controlled trials (RCTs) published before 24 October 2019 were identified by a systematic literature review. Short-term (12-16 weeks) efficacy (Investigator's Global Assessment [IGA] and Eczema Area and Severity Index [EASI] responses), patient-reported outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
57
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 50 publications
8
57
1
2
Order By: Relevance
“…The increased effectiveness of dupilumab in clinical practice was reflected in a higher number of patients who achieved EASI-50 and a higher reduction in SCORAD and DLQI. Clinical improvement with dupilumab was similar to that observed in previous studies in real-life settings (achieving EASI-50 in around 80% at week 12–16) [ 31 , 32 , 33 ] and higher than in clinical trials [ 34 ]. As in previous studies, we found that dupilumab improves patient quality of life [ 35 ].…”
Section: Discussionsupporting
confidence: 86%
“…The increased effectiveness of dupilumab in clinical practice was reflected in a higher number of patients who achieved EASI-50 and a higher reduction in SCORAD and DLQI. Clinical improvement with dupilumab was similar to that observed in previous studies in real-life settings (achieving EASI-50 in around 80% at week 12–16) [ 31 , 32 , 33 ] and higher than in clinical trials [ 34 ]. As in previous studies, we found that dupilumab improves patient quality of life [ 35 ].…”
Section: Discussionsupporting
confidence: 86%
“…This indirect comparison analysis found that baricitinib and dupilumab might have similar efficacy across EASI75, ≥ 4-point improvement in itch NRS, and DLQI improvement (baricitinib 4 mg) after 16 weeks of treatment, confirming the findings of a recently published network meta-analysis (NMA) and extending them to an earlier time point (week 4) [ 14 ].…”
Section: Discussionsupporting
confidence: 85%
“…Silverberg et al. published an NMA comparing systemic therapies in monotherapy and combination therapy for AD but did not include data after October 2019, and so excluded the phase 3 upadacitinib trial program [ 46 ]. This analysis focused only on targeted therapies studied as monotherapy and considered the primary endpoints used in clinical trials (IGA 0/1 and EASI-75) and itch, the hallmark symptom of AD.…”
Section: Discussionmentioning
confidence: 99%